A MODIFIED GIFFLER AND THOMPSON ALGORITHM COMBINED WITH DYNAMIC SLACK TIME FOR SOLVING DYNAMIC SCHEDULE PROBLEMS - Tanti Octavia (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2003)
A Modified Giffler and Thompson algorithm combined with dynamic slack time is used to allocate machines resources in dynamic nature. It was compared with a Real Time Order Promising (RTP) algorithm. The performance of modified Giffler and Thompson and RTP algorithms are measured by mean tardiness. The result shows that modified Giffler and Thompson algorithm combined with dynamic slack time provides significantly better result compared with RTP algorithm in terms of mean tardiness.